Method for preparing YBCO (Yttrium Barium Copper Oxide) nanowire at low temperature and low air pressure
By using low-temperature and low-pressure ICP-RIE technology in the preparation process of YBCO nanowires, the problems of difficulty in preparing YBCO nanowires and unstable performance in the existing technology are solved, and efficient and low-damage nanowire preparation is achieved, which significantly improves the electrical performance and preparation consistency of the nanowires.
Patent Information
- Application Number
- CN202510069492.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-16
AI Technical Summary
It is difficult to effectively prepare high-quality YBCO nanowires in the prior art, especially in maintaining superconducting properties and avoiding oxygen loss and chemical erosion caused by thermal effects.
Low-temperature and low-pressure inductively coupled plasma reactive ion etching (ICP-RIE) technology is used to accurately regulate the temperature and air pressure conditions of the sample table, reduce thermal damage and non-ideal lateral etching effects, and improve etch selectivity and electrical performance of nanowires.
The electrical properties of YBCO nanowires are significantly improved, the morphological uniformity and consistency of electrical characteristics of the nanowires are ensured, thermal damage during the etching process is reduced, and high-precision and highly selective nanowire preparation is achieved.
Smart Images

Figure CN119900005A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of single-photon detection, and in particular relates to a method for preparing YBCO nanowires at low temperature and low pressure. Background Art
[0002] Superconducting nanowire single photon detectors (SNSPDs) have excellent performance (detection efficiency > 98%, count rate ≥ 1.5 GHz, dark count rate < 6 × 10 -6 / s, time jitter <3ps, broadband response range from X-ray to 10.6μm, maximum array size up to 400000 pixels) and has attracted increasing attention, and its application areas are rapidly expanding. SNSPDs based on high-temperature superconductors are expected to operate at liquid nitrogen temperatures, which greatly simplifies the cryogenic requirements compared to low-temperature superconducting SNSPDs that rely on liquid helium. 8-δ The SNSPD has achieved single-photon response at 25K, but the development of high-temperature superconducting SNSPDs working at higher temperatures still faces challenges. 7-δ (YBCO) due to its higher critical temperature (T c =92K), large-area epitaxial growth (inch-level) and shorter electron-phonon relaxation time have made it the preferred thin film material for the preparation of high-temperature SNSPDs.
[0003] The core step of high-temperature SNSPDs devices is to prepare high-quality YBCO nanowires. The sensitivity of YBCO superconducting films makes the preparation of high-quality ultra-thin and ultra-narrow nanowires a huge challenge. The chemical properties of YBCO are unstable, and oxygen atoms easily migrate and diffuse outward along the Cu-O chain. The exposed YBCO film will gradually lose the optimal oxygen doping when exposed to the air, resulting in performance degradation. It is also extremely sensitive to defects and disorder due to its very short coherence length and the d-wave symmetry of the superconducting order parameter. At the same time, it is difficult to remove its metal components by ordinary etching methods, and the etching rate is slow. Therefore, YBCO thin film nanowires are very likely to fail during the entire patterning process due to thermal effects that cause oxygen loss in the superconducting layer, direct corrosion of chemicals and ions, and other reasons. It is difficult to produce nanowires with good performance and uniformity without serious degradation of the film.
[0004] At present, the patterning process for preparing ultrathin YBCO nanowires mainly relies on focused ion beam (FIB), reactive ion etching (RIE), ion beam etching (IBE) and ion irradiation. Among them, FIB and IBE combined with electron beam lithography are the most common and successful technologies, but FIB has low efficiency and is difficult to array, and the IBE process is complex and has poor controllability. In addition, when using RIE for etching, the etching rate of YBCO is very slow, the reaction products are difficult to volatilize, and are easily adsorbed on the surface of YBCO to hinder etching, resulting in poor etching effect. In addition, there are new patterning processes such as porous alumina templates, porous SrTiO3 (STO) insulating film templates, amorphous STO templates, atomic force microscope contact lithography and superlattice-nanowire pattern transfer, but the application efficiency is low. In addition, in the field of micro-nano processing of semiconductors and other materials, atomic layer etching (ALE) technology and inductively coupled plasma reactive ion etching (ICP-RIE) technology have also been widely used. Especially in the precise processing of ultra-thin materials and nanostructures, these two technologies have significant advantages, so they have also been considered for the preparation of YBCO nanowires. However, the application of ALE technology in the preparation of ultra-thin YBCO nanowires is greatly limited, mainly because it is usually carried out at a higher temperature (above 150°C), and YBCO films are extremely sensitive to temperature. Improper temperature control and excessive oxygen partial pressure may lead to a decrease in superconducting properties. In addition, ALE technology relies on precise gas control, and atomic-level removal is achieved by alternating exposure to etching gas and removal gas, which makes the etching rate slow. Each reaction cycle may introduce errors, affecting the morphology and superconducting properties. As early as 2001, a study used ICP-RIE technology to etch 500nm thick YBCO, and found that the etching rate was too fast and not suitable for processing thin films. There has been no progress in the research of ICP-RIE technology in the preparation of YBCO nanowires.
[0005] In general, although there are various methods for preparing YBCO nanowires, the process is relatively complex and has poor stability. During the patterning process, it is very easy to cause oxygen loss, chemical substances or ions to directly corrode due to thermal effects, which can cause the superconducting layer to fail. Therefore, in order to meet the high quality requirements of high-performance SNSPDs for superconducting nanowires, it is urgent to develop an efficient, low-damage, and stable nanowire preparation process. Summary of the invention
[0006] In view of the problems existing in the background technology, the purpose of the present invention is to provide a method for preparing YBCO nanowires at low temperature and low pressure. The method adopts inductively coupled plasma reactive ion etching (ICP-RIE) technology, and by accurately controlling the temperature and pressure conditions of the sample stage during etching, the etching selectivity is improved, the thermal damage and non-ideal lateral etching effects during the etching process are reduced, and the electrical properties of the prepared ultra-thin YBCO nanowires are significantly improved, which lays a good foundation for the preparation of high-temperature SNSPDs and is of great significance in the fields of superconducting devices, quantum computing and nanoelectronics.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for preparing YBCO nanowires at low temperature and low pressure, comprising the following steps:
[0009] Step 1: growing a YBCO thin film on the substrate surface;
[0010] Step 2: Attach an electrode pattern mask to the sample surface, and then use electron beam evaporation to prepare the metal electrode. After the electrode preparation is completed, remove the mask, and then use plasma enhanced atomic layer deposition to grow a dense aluminum oxide protective layer;
[0011] Step 3: Prepare YBCO microwire devices by using ultraviolet lithography combined with low-temperature and low-pressure inductively coupled plasma reactive ion etching to locate the area where the nanowires are to be made;
[0012] Step 4: Prepare the desired nanowires using electron beam lithography combined with low-temperature and low-pressure inductively coupled plasma reactive ion etching.
[0013] Furthermore, in step 1, the growth substrate is preferably a strontium titanate, magnesium oxide or lanthanum aluminate substrate.
[0014] Furthermore, in step 1, the growth method of the YBCO thin film is preferably a DC magnetron sputtering method.
[0015] Furthermore, in step 1, when the thickness of the grown YBCO film is 10 nm or less, an amorphous YBCO protective layer is in-situ grown on the surface of the YBCO film, and the thickness of the amorphous YBCO protective layer is 6-10 nm to prevent the YBCO film from being degraded by contact with the atmospheric environment during subsequent processing. The growth method is preferably DC magnetron sputtering.
[0016] Furthermore, in step 2, the vacuum degree of the electron beam evaporation system chamber is less than 5×10 -6 mbar, the evaporation rate is
[0017] Furthermore, in step 3 and step 4, the parameters of low-temperature and low-pressure inductively coupled plasma reactive ion etching are the same, the sample stage temperature is -20 to -10°C, the etching gas is CHF3 / Ar mixed etching gas, the ICP power is 800-1200W, the RF power is 80-120W, and the etching pressure is 1-3mTorr.
[0018] Furthermore, in step 4, the thicker the YBCO film is, the longer the inductively coupled plasma reactive ion etching time is; for a YBCO film with a thickness of 15 nm, the inductively coupled plasma reactive ion etching time is 90s to 135s.
[0019] Furthermore, in step 3, the specific process of UV lithography is: after cleaning the sample surface, spin-coating photoresist and heating the photoresist; then UV exposure and development are performed to etch the micron area of the nanowire to be made connected to the electrode channel, and then the photoresist is removed.
[0020] Furthermore, in step 4, the specific process of electron beam lithography is: after cleaning the sample surface, spin-coat photoresist and heat and bake the resist; then spin-coat conductive resist and heat and bake the resist; then perform electron beam lithography to prepare nanowire patterns, perform etching after development, and finally perform resist stripping.
[0021] The mechanism of the present invention is:
[0022] In the etching process of YBCO thin film, temperature and pressure conditions have a key influence on superconducting properties and etching effect. First, low temperature conditions help to slow down heat accumulation and prevent changes in oxygen content in the YBCO film, thereby ensuring that it maintains the optimal oxygen doping state throughout the etching process and keeps the superconducting properties stable. 7-δThe superconductivity of YBCO is extremely sensitive to oxygen content. The range of δ values corresponding to the best superconducting performance is small. Excessive temperature will cause oxygen dispersion (deoxygenation), resulting in degradation of superconducting properties. At the same time, the ion energy is reduced under low temperature conditions, the reaction rate is slowed down, and excessive etching of the film sidewalls is reduced, which helps to reduce damage to the edges of nanowires. Secondly, under low pressure, the molecular free path is long, the plasma density is low, the energy of the ion beam is more concentrated, and the high-energy plasma bombardment leads to enhanced etching directionality and longitudinal etching, which not only helps to remove by-products on the surface of the YBCO film (due to the complex composition of these by-products and the low saturated vapor pressure, the passivation they form on the surface will hinder the continued etching), improve the etching rate and uniformity, and combined with low temperature conditions, it can more effectively reduce the damage caused by lateral etching. In addition, high-energy plasma bombardment under low pressure will generate a lot of heat, so low temperature conditions are more necessary to avoid thermal damage. The etching technology under the combination of low temperature and low pressure significantly optimizes the etching effect of YBCO nanowires by slowing down heat accumulation, efficiently removing by-products, improving etching accuracy, and stabilizing superconducting properties, achieving high-precision and high-selectivity nanowire preparation while ensuring the consistency and stability of electrical properties.
[0023] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0024] The preparation method of the present invention enhances the controllability and consistency of the etching process, ensures the uniformity of the nanowire's morphology and the consistency of its electrical properties, and effectively reduces the damage caused by the thermal effect during the etching process by precisely controlling the temperature and pressure parameters, thereby obtaining a very small lateral etching damage width (about 15nm), thereby increasing the limit processing size of the nanowire, because if the damage width is large, nanowires with small line widths cannot be prepared. The thickness of the nanowires prepared by the method of the present invention is as low as 5nm, and the width can be as narrow as 68nm, and the excellent morphology and electrical properties of the nanowires are ensured; at the same time, the switching current (I s ) coefficient of variation is less than 6% and the coefficient of variation of resistance-temperature (RT) characteristics is less than 1%, demonstrating its excellent uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the nanowire switching current (I) obtained in Example 1 under different etching time conditions at 4K s ) and width (a) and the relationship between the actual etching damage width and etching time obtained by linear fitting (b);
[0026] Figure 2 The schematic diagram and actual SEM image of the nanowire structure prepared in Example 2;
[0027] Figure 3is the nanowire switching current (I) obtained in Example 2 under different etching time conditions at 4K s ) and width (a) and the relationship between the actual etching damage width and etching time obtained by linear fitting (b);
[0028] Figure 4 The resistance-temperature (R / R) of the nanowire with a width of 400 nm prepared in Example 1 and the microwire with a width of 30 μm prepared in Comparative Example 1 is 300K -T) Characteristics comparison chart;
[0029] Figure 5 The nanowire switching current (I) at 4K obtained in Example 1 and Comparative Example 2 s ) and width and the actual etching damage width obtained by linear fitting;
[0030] Figure 6 is the nanowire switching current (I s ) versus width;
[0031] Figure 7 The nanowire switching current (I) at 4K obtained in Example 1 and Comparative Example 4 s ) versus width;
[0032] Figure 8 is the nanowire switching current (I) at 4K obtained in Example 3 s ) and uniformity analysis of resistance-temperature (RT) characteristics. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.
[0034] Example 1
[0035] A method for preparing YBCO nanowires at low temperature and low pressure, comprising the following steps:
[0036] Step 1: Prepare YBCO thin film on the substrate surface:
[0037] A strontium titanate substrate was selected and cleaned (acetone megasonic for 5 minutes, isoacetone megasonic for 5 minutes, isopropanol rinsed, and dried with a nitrogen gun); a YBCO film with a thickness of 15 nm was grown on the substrate surface by a DC magnetron sputtering method, the cavity was filled with a mixed gas of O2:Ar=1:3, the gas pressure was 30Pa, the sputtering power was 125W, and the substrate temperature was 802℃; after the sputtering was completed, the heating was turned off, and the sample was taken out after cooling to room temperature;
[0038] Step 2: Attach a stainless steel mask with electrode pattern to the surface of the YBCO film of the sample, and then prepare the metal electrode (Ag / Au: 20nm / 20nm) by electron beam evaporation. The vacuum degree of the cavity is less than 5×10 -6 mbar, the evaporation rate is
[0039] After the electrode preparation is completed, the mask is removed, and then a 10nm dense aluminum oxide protective layer is grown on the entire device surface using plasma enhanced atomic layer deposition to prevent the YBCO film from being exposed to the atmospheric environment and degrading during subsequent processing;
[0040] Step 3: UV photolithography of the sample obtained in step 2: first clean the surface of the sample obtained in step 2; then place it on a hot plate at 110°C for pre-baking for 1 minute; spin-coat AZ5214 photoresist (6000rmp, 60s); bake the photoresist on a hot plate at 110°C for 1 minute; after UV exposure, develop it with ZX238 for 45s to locate the micron area of the nanowire to be made that is connected to the electrode channel; use low-temperature and low-pressure inductively coupled plasma reactive ion etching on the sample after UV photolithography to obtain a micron line with a width of 30μm: use a mixed etching gas (CHF3 / Ar: 10 / 10sccm), an ICP power of 1000W, an RF power of 100W, an etching pressure of 1mTorr, and maintain the sample stage temperature at -20°C to prevent thermal damage caused by the etching process; after etching, remove the UV photoresist, the process is: soak in acetone for 10min, megasonic for 20min, rinse with isopropanol and blow dry with a nitrogen gun;
[0041] Step 4: Electron beam lithography was performed on the sample obtained in step 3: the sample surface obtained in step 3 was first cleaned, and then placed on a 180°C hot plate for pre-baking for 1 min; ZEP-520A electron beam photoresist was spin-coated (7000 rpm, 60 s), and the glue was baked on a 180°C hot plate for 3 min; conductive carbon glue was spin-coated (4000 rpm, 60 s), and the glue was baked on a 110°C hot plate for 2 min; electron beam lithography was used at an acceleration voltage of 20 kV and an exposure dose of 30 μC / cm 2 The conductive carbon glue was removed by rinsing with deionized water, and the surface was dried with a nitrogen gun, and then developed with a ZED-N50 developer at room temperature for 3 min, followed by immersion in isopropanol for 15 s, rinsing with deionized water, and then drying with a nitrogen gun;
[0042] The exposed samples were subjected to low temperature (-20°C) and low pressure (1mTorr) inductively coupled plasma reactive ion etching with etching times of 90s, 105s, 120s and 135s, respectively, to obtain single nanowires with a length of 1μm and widths of 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 700nm, 750nm, 800nm, 900nm, 1μm, 1.1μm, 1.5μm, 2μm, 2.5μm, 3μm and 6μm. The debonding process was UV treatment for 5min, acetone immersion for 10min, megasonic treatment for 20min, isopropanol rinsing and drying with a nitrogen gun.
[0043] Example 2
[0044] YBCO nanowires were prepared according to the steps of Example 1, and step 1 was adjusted as follows: a YBCO film with a thickness of 8 nm was grown on the surface of the substrate by a DC magnetron sputtering method; after the film growth was completed, the chamber was allowed to cool to room temperature, and then a 10 nm thick amorphous YBCO protective layer was grown on the YBCO film under the same gas conditions and sputtering power to prevent the ultra-thin YBCO film from being degraded by contact with the atmospheric environment during subsequent processing;
[0045] Step 4 was adjusted as follows: inductively coupled plasma reactive ion etching was performed on the sample after electron beam lithography, the sample stage temperature was -20°C, the chamber pressure was 1 mTorr, the etching time was 110 s, 115 s and 120 s respectively, and single nanowires with widths of 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm and 500 nm were obtained.
[0046] Example 3
[0047] YBCO nanowires were prepared according to the steps of Example 1;
[0048] Only step 1 is adjusted as follows: a YBCO film with a thickness of 10 nm is grown on the substrate surface by a DC magnetron sputtering method; after the film growth is completed, the chamber is allowed to cool to room temperature, and then a 10 nm thick amorphous YBCO protective layer is grown on the YBCO film under the same gas conditions and sputtering power to prevent the ultra-thin YBCO film from being degraded by contact with the atmospheric environment during subsequent processing;
[0049] Only step 4 was adjusted as follows: 15 single nanowires with widths of 400 nm, 600 nm, 800 nm and 1 μm were prepared on the same sample.
[0050] Example 4
[0051] YBCO nanowires were prepared according to the steps of Example 1, except that the etching pressure of the inductively coupled plasma reactive ion etching in step 4 was adjusted to 3 mTorr, and the other steps remained unchanged.
[0052] This embodiment can also realize the preparation of nanowires.
[0053] Comparative Example 1
[0054] YBCO microwires were prepared according to the steps of Example 1, except that step 4 was omitted and the remaining steps remained unchanged;
[0055] Comparative Example 2
[0056] YBCO nanowires were prepared according to the steps of Example 1, except that step 4 was adjusted as follows: the inductively coupled plasma reactive ion etching temperature was 20° C., and single nanowires with widths of 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm and 600 nm were prepared;
[0057] Comparative Example 3
[0058] YBCO nanowires were prepared according to the steps of Example 1, except that step 4 was adjusted as follows: the inductively coupled plasma reactive ion etching pressure was 5 mTorr, the etching time was increased from 120 s to 300 s, and then increased by 30 s successively, to prepare single nanowires with widths of 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm and 600 nm.
[0059] Comparative Example 4
[0060] YBCO nanowires were prepared according to the steps of Example 1, except that step 4 was adjusted as follows: the inductively coupled plasma reactive ion etching pressure was 0.6 mTorr, and single nanowires with widths of 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm and 600 nm were prepared.
[0061] Example 1 The superiority of the present invention in efficiently preparing high-quality YBCO nanowires was verified by preparing nanowires on a 15 nm thick YBCO film without an in-situ amorphous YBCO protective layer. In order to evaluate the superconducting properties of the nanowires, the current-voltage (IV) characteristics under different conditions were measured, and the key switching current (I s ) value, J c =I s / wd, where w is the width of the nanowire, d is the thickness of the nanowire, J c The higher the value, the better the quality of the nanowires. s This indicator directly reflects the quality and uniformity of the nanowires. Figure 1(a) shows the I at 4K with different etching times s The linear relationship between the width of the nanowires ranges from 300nm to 6μm. Under different etching times, I s The result is almost unchanged, which is consistent with the linear relationship of the nanowire width, indicating that the superconducting current is evenly distributed along the nanowire, that is, the uniformity of the nanowire is good. The fitted extrapolation line of each etching time intersects the positive X-axis at almost the same point (the intersection value is defined as the nanowire edge damage width, which quantifies the nanowire edge damage caused by etching), which is very close to zero, indicating that the superconducting current is evenly distributed along the nanowire, that is, the uniformity of the nanowire is good. Figure 1 The edge damage width is smaller during the etching process shown in (a). Figure 1 (b) It can be seen that with the increase of etching time, I s The value remains relatively stable, and the edge damage width increases slightly (from 20nm to about 60nm), which shows that the edge damage width can be fine-tuned by controlling the etching time. The longer the etching time, the larger the edge damage width, and the narrower the actual effective width of the nanowire.
[0062] Example 2 further verifies the effectiveness of the present invention in preparing high-quality ultrathin YBCO nanowires by patterning nanowires on an 8 nm thick YBCO film with an in-situ amorphous YBCO protective layer. Figure 2 (a) shows the fabricated nanowire structure. The linear length of the nanowire is 1 μm. The transition regions where the nanowires connect to the electrodes are designed to be rounded to minimize the current crowding effect, which would otherwise reduce the I s . Figure 2 (b) shows a scanning electron microscope (SEM) image of a YBCO nanowire with a width of 300 nm and provides a magnified view of the white rectangular area, where the clearly defined etching profile along the edge of the nanowire demonstrates the high precision of the patterning process, ensuring the ideal geometry and structure of the YBCO nanowire.
[0063] Figure 3 (a) shows the relationship between the nanowire width (from 150 nm to 500 nm) and I s The linear relationship between Figure 2 (a) shows a similar trend, and Figure 3 (b) shows that the edge damage of the nanowire is relatively stable under different etching times, and the width of the nanowire with the smallest edge damage is only about 15nm. Different from Example 1, the surface of the 8nm thick YBCO ultra-thin film in Example 2 is covered with a 10nm thick amorphous YBCO protective layer, which effectively avoids the damage caused by the nanowire preparation process. The results of Example 2 and Comparative Example 1 are shown in Figure 2. Figure 4 As shown, the R / R of 30μm wide microwires and 400nm nanowires on 8nm thick YBCO ultra-thin film 300K-T characteristics are almost the same, critical temperature (T c0 ) only slightly decreases, and the superconducting transition width shows a negligible widening, demonstrating that the YBCO ultrathin film retains excellent electrical properties even after the preparation of narrow linewidth nanowires.
[0064] Figure 5 The results of Example 1 and Comparative Example 2 are compared. At -20°C, the nanowire I s The linear relationship with the width is clear and consistent, and nanowires with a width as low as 150nm and damage as low as 22nm can be obtained; however, at 20℃, it is difficult to prepare nanowires with a width less than 300nm, the edge damage width increases to 248nm, and the nanowire yield is low. s The linear relationship with the width also becomes worse. This result proves that low temperature conditions can effectively reduce the thermal damage and material degradation that may occur during the etching process, and can enhance the selectivity of the etching process, thereby improving the etching accuracy and ensuring low loss and efficient preparation of ultra-thin nanowires.
[0065] Figure 6 The results of Comparative Example 3 are shown. When the etching pressure is increased to 5 mTorr, the etching effect fails to reach the expected level. For example, the I of the YBCO nanowire with a thickness of 15 nm and a width of 300 nm is s It should be around 1.5 mA, but at this time the nanowire I s It is stable at 8mA and does not change with the width of the nanowire, indicating that the etching effect is very small. The YBCO film in the exposed area during the patterning of the nanowire is not etched through, and adjusting the etching time cannot improve this problem. After reducing the gas pressure to 0.6mTorr, Figure 7 The comparison results of Example 1 and Comparative Example 4 are shown. The low pressure leads to the nanowire I under the same conditions. s The value is reduced, and nanowires with a width less than 600nm will be damaged. This shows that the etching pressure has a decisive influence on the etching effect. Higher gas pressure leads to increased collisions of etching gas molecules and reduced directionality and orientation of ions, making the etching more diffuse and difficult to accurately etch nanowires. At the same time, the energy loss of ions during transmission is large, resulting in reduced etching efficiency. Although low gas pressure can help improve the directionality and energy control of ions, if the gas pressure is too low, the ion energy will be too high and excessive etching will cause damage. Under low pressure, the ion beam may be too concentrated, which can easily lead to nanowire breakage or uneven etching edges, thereby affecting the electrical properties of the nanowires and reducing I s .
[0066] Finally, in Example 3, 15 nanowires of 4 different widths were prepared on a 10 nm thick YBCO film with an in-situ protective layer, further verifying the high efficiency and excellent uniformity of the YBCO nanowires prepared by the present invention. Figure 8 As shown in (a), the on-chip uniformity of nanowires with widths of 400nm, 600nm, 800nm, and 1μm is very good. s The average values were 0.9, 1.48, 2.1 and 2.7 mA, respectively, and the coefficient of variation was less than 6%. Figure 8 The coefficient of variation of the resistance-temperature (RT) characteristics of the 800 nm wide nanowire presented in (b) is less than 1%, demonstrating its excellent uniformity. The large-scale preparation of highly uniform nanowires is a solid foundation for preparing array devices and expanding their applications.
[0067] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.
Claims
1. A method for preparing YBCO nanowires at low temperature and low pressure, characterized in that: The following steps are involved: Step 1: growing a YBCO thin film on the substrate surface; Step 2: Attach an electrode pattern mask to the sample surface, and then use electron beam evaporation to prepare the metal electrode. After the electrode preparation is completed, remove the mask, and then use plasma enhanced atomic layer deposition to grow a dense aluminum oxide protective layer; Step 3: Prepare YBCO microwire devices by using ultraviolet lithography combined with low-temperature and low-pressure inductively coupled plasma reactive ion etching to locate the area where the nanowires are to be made; Step 4: Prepare the desired nanowires using electron beam lithography combined with low-temperature and low-pressure inductively coupled plasma reactive ion etching.
2. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 1, the growth substrate is a strontium titanate, magnesium oxide or lanthanum aluminate substrate.
3. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 1, the YBCO thin film is grown by direct current magnetron sputtering.
4. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 1, when the thickness of the grown YBCO film is 10 nm or less, an amorphous YBCO protective layer is in-situ grown on the surface of the YBCO film. The thickness of the amorphous YBCO protective layer is 6-10 nm, and the growth method is DC magnetron sputtering.
5. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 2, the vacuum degree of the electron beam evaporation system chamber is less than 5×10 -6 mbar, the evaporation rate is 6. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 3 and step 4, the parameters of low-temperature and low-pressure inductively coupled plasma reactive ion etching are the same, the sample stage temperature is -20 to -10°C, the etching gas is CHF3 / Ar mixed etching gas, the ICP power is 800-1200W, the RF power is 80-120W, and the etching pressure is 1-3mTorr.
7. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 4, the thicker the YBCO film is, the longer the inductively coupled plasma reactive ion etching time is; for a YBCO film with a thickness of 15 nm, the inductively coupled plasma reactive ion etching time is 90s to 135s.
8. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 3, the specific process of UV lithography is: after cleaning the sample surface, spin-coating photoresist and heating the photoresist; then UV exposure and development are performed to etch the micron area of the nanowire to be made connected to the electrode channel, and then the photoresist is removed.
9. The method for preparing YBCO nanowires at low temperature and low pressure as claimed in claim 1, characterized in that: In step 4, the specific process of electron beam lithography is: after cleaning the sample surface, spin-coat photoresist and heat and bake the resist; then spin-coat conductive resist and heat and bake the resist; then perform electron beam lithography to prepare nanowire patterns, perform etching after development, and finally perform resist stripping.
Citation Information
Patent Citations
Preparation method of thermosensitive-film infrared detector
CN102315329A
Preparation method of novel nano structure of superconducting thin film
CN116261391A
Air Cell Thermal Isolation for a Memory Array Formed of a Programmable Resistive Material
US20080266940A1